An Analysis of Taboo Words in Rich Brian’s Song Lyrics - Derli Elsa Putri; Barnabas S.; Imranuddin . (Universitas Bengkulu, 2019)
This research aimed at investigating taboo words in Rich Brian’s song lyrics. The researcher described what kinds, functions, and meanings of taboo words used in Rich Brian’s song lyrics. The sample of this research was five Rich Brian’s song lyrics that collected by using simple random sampling. The researcher employed a theory from Batistella to describe the kinds of taboo words and a theory from Wardhaugh to describe the functions of taboo words. Then, in finding the meaning of taboo words in Rich Brian’s song lyrics the researcher employed some dictionaries, internet and article as well to support the data. In addition, this research was completed assisted by co-researcher. The result showed that there were 89 taboo words found in those five song lyrics where obscenity was the highest kind of taboo words which mentioned 49 times (45%) and profanity was the least which mentioned 6 times (7%). Then, in functions of taboo words showing contempt became the commonly used while mocking authority became the least used. Furthermore, according to the sociolinguistic point of view this kind of music surely is not Indonesian culture but it is more to western culture where many rapper come from there and it usually spoken by specific class of people.